Puerarin: A protective drug against ischemia-reperfusion injury - Gao, Minglang; Zhang, Ziyao; Lai, Kai; Deng, Yu; Zhao, Chuanbing; Lu, Zilong; Geng, Qing (Frontiers in Pharmacology, 2022)
Ischemia-reperfusion (I/R) is a pathological process that occurs in numerous organs throughout the human body and is frequently associated with severe cellular damage and death. Puerarin is an isoflavone compound extracted from the root of Pueraria lobata and has pharmacological effects such as dilating cerebral vessels and anti-free radical generation in cerebral ischemic tissues. With the deepening of experimental research and clinical research on puerarin, it has been found that puerarin has a protective effect on ischemia-reperfusion injury (IRI) of the heart, brain, spinal cord, lung, intestine and other organs. In summary, puerarin has a vast range of pharmacological effects and significant protective effects, and it also has obvious advantages in the clinical protection of patients with organ IRI. With the deepening of experimental pharmacological research and clinical research, it is expected to be an effective drug for IRI treatment. In this review, we summarize the current knowledge of the protective effect of puerarin on I/R organ injury and its possible underlying molecular mechanisms.